Domingo de Soto y la renovación tomista - Simó, Jaime Mercant (Sapientia, 2023)
In the Spain of the first half of the 16th century, the academic phenomenon of a theological renewal of a Thomistic character was experienced, especially at the University of Salamanca. This article presents the role played by the Dominican Domingo de Soto in this renewal, following in the wake of Francisco de Vitoria. The work is structured in three moments, corresponding to three vital stages of Master Soto: his personal conversion from nominalism to Thomism; his decisive work in implanting the Thomistic doctrine in the University of Tormes; and, finally, because of the above, the consolidation and triumph of Thomism itself in the theological chairs.